Clinical outcome of fresh and vitrified-warmed blastocyst and cleavage-stage embryo transfers in ethnic Chinese ART patients - Tong Guo; Cao Shan; Wu Xun; Zhang Jun; Cui Ji; Heng Boon; Ling Xiu (Journal of Ovarian Research, 2012)
Abstract Objectives This study sought to evaluate the outcome of fresh and vitrified-warmed cleavage-stage and blastocyst-stage embryo transfers in patients undergoing ART treatment within an ethnic Chinese population. Study design We compared the clinical results of embryo transfer on the 3rd (cleavage stage) or 5th (blastocyst stage) day after oocyte retrieval, including clinical pregnancy rates, implantation rates and multiple pregnancy rates. Results Our data showed that blastocyst transfer on day 5 did not significantly increase clinical pregnancy rate (41.07% vs 47.08%, p>0.05) and implantation rate (31.8% vs 31.2%, p>0.05) in patients under 35 years of age, in comparison with day 3 cleavage stage embryo transfer. In patients older than 35 years of age, the clinical pregnancy rate after blastocyst transfer was slightly decreased compared with cleavage stage embryo transfer (33.33% vs 42.31%, p>0.05). Unexpectedly, It was found that vitrified-warmed blastocyst transfer resulted in significantly higher clinical pregnancy rate (56.8%) and implantation rate (47%) compared with fresh blastocyst transfer in controlled stimulation cycles (41.07% and 31.8%, respectively). For patients under 35 years of age, the cumulative clinical pregnancy rate combining fresh and vitrified-warmed blastocyst transfer cycles were significantly higher compared to just cleavage-stage embryo transfer (70.1% versus 51.8%, p<0.05). However, the cumulative multiple pregnancy rates showed no significant difference between the two groups. Conclusions In an ethnic Chinese patient population, fresh blastocyst transfer does not significantly increase clinical pregnancy rate. However, subsequent vitrified-warmed blastocyst transfer in a non-controlled ovarian hyperstimulation cycle dramatically improves clinical outcomes. Therefore, blastocyst culture in tandem with vitrified-warmed blastocyst transfer is recommended as a favourable and promising protocol in human ART treatment, particularly for ethnic Chinese patients.